Newton’s method for generalized equations: a sequential implicit function theorem - Dontchev, A. L.; Rockafellar, R. T. (Mathematical programming, 2010)
In an extension of Newton’s method to generalized equations, we carry further the implicit function theorem paradigm and place it in the framework of a mapping acting from the parameter and the starting point to the set of all associated sequences of Newton’s iterates as elements of a sequence space. An inverse function version of this result shows that the strong regularity of the mapping associated with the Newton sequences is equivalent to the strong regularity of the generalized equation mapping.